UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT DAUN UBI JALAR UNGU (Ipomea batatas L.) DENGAN MENGGUNAKAN METODE DPPH - Alfiyah Cahyani Rhomah; Yoni Rina Bintari; Dian Novita Wulandari (Jurnal Insan Farmasi Indonesia, 2025)
Purple sweet potato leaves (Ipomea batatas L) have contained various bioactive compounds such as phenolic and caffeolyquinic acid has a potential pharmacological as an antioxidant. The study aimed to investigate of antioxidant potential of the ethyl acetate fraction of purple sweet potato leaves using DPPH method. It began with extracting the simplicia of purple sweet potato leaves using the Ultrasound-Asissted-Extraction (UAE) method with ethanol p.a, then multi-stage liquid-liquid fractionation with non-polar to polar solvents so that an ethyl acetate fraction was obtained as a sample. The samples are measured for antioxidant activity using the DPPH method results expressed as the IC50 value. Phytochemical screening showed that ethyl acetate fraction of I.batatas leaves was positive contained phenolic compounds and had a potential antioxidant activity of (IC50 = 5.27 μg/ml) which was included in the very strong category.